Comprehensive issues of employment and labour law practice for modern business in Tanzania - Ally Kileo (South Africa LexisNexis, 2023)
The book is centrally focused on discussing matters in relations to human resources management which is a very important function in every organization. Without human resources management, companies would not be able to effectively recruit and retain employees, improve and enhance the organization, and they wouldn?t be able to maintain a healthy, accepting workplace culture and environment. Additionally human resources is a costly element for any business and with our current laws should compliance not be taken into account a company will have to deal with all associated costs as part of their human resources budget.
Keywords: Employment